Homœopathy in the treatment of haemophilia - Hunton, Mollie (British Homeopathic Journal, 1991)
Six patients with haemophilia were treated with homœopathic medicines. A rational attempt has been made to improve their general health, cope with side effects of Factor VIII, cut down the bleeding episodes and reduce the amount of Factor VIII needed. This has necessitated a search of the homœopathic literature (British Homœopathic Journal) and a study of the repertories and materia medicas. Each patient treated has had aspects of his health improved, and the overall impression is that less Factor VIII was needed.